Mengenal Budaya “Pukol Sagu” Orang Maluku - Novita L. Ruhukail (Journal on Education, 2023)
This research aims to preserve the culture of "pukol sago", the Moluccas, so that it is not crushed by the changes in time, and it is already an obligation, when as the children and grandchildren of the Moluccas, this culture is reintroduced to the Millennium generation. This study used a survey method with field observations, where surveys and observations were carried out in several villages on Ambon Island, where sago farmers carry out sago processing, such as: Tulehu Village, Waai Village and Waipatili Hamlet, Hitu Village. Then took data on sago processing activities carried out by sago farmers, using interview techniques based on prepared questionnaires, as well as taking documentation related to the research. Apart from that, in this study, secondary data was also collected, in the form of the results of previous research or previous scientific work that had been carried out at the research site in question and also in the form of literature that had relevance to this research. Research results from the three research sites, namely Tulehu Village, Waai Village and Waipatili Hamlet, Hitu Village, show that generally a person's level of education will affect the way and pattern of life, this also occurs in sago farming communities, where the level of education is below on average it has an impact on the way they carry out sago management work "pukol sago", where generally the sago management techniques that are carried out are still traditional to semi-mechanical. As for the processing resistance of sago or "pukol sago", these include: logging, cutting/splitting of sago stems, destruction of pith/contents of sago stems, extraction of sago starch, storage and deposition of starch, packaging of wet sago starch and drying of sago starch.